2013
DOI: 10.1891/0886-6708.vv-d-12-00145
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Firearm-Related Violence Against Canadian Women: Did Tightening Gun Laws Have an Impact on Women’s Health and Safety?

Abstract: Domestic violence remains a significant public health issue around the world, and policy makers continually strive to implement effective legislative frameworks to reduce lethal violence against women. This article examines whether the 1995 Firearms Act (Bill C-68) had a significant impact on female firearm homicide victimization rates in Canada. Time series of gender-disaggregated data from 1974 to 2009 were examined. Two different analytic approaches were used: the autoregressive integrated moving average (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
(26 reference statements)
2
9
0
Order By: Relevance
“…Mauser and Holmes also found no association with this legislation and firearm homicide [25]. Examination of all three legislative efforts by Langmann resulted in no finding of any beneficial association with overall firearm homicide and spousal homicide by firearm, and McPhedran and Mauser found no association between legislation and homicide of female spouses by firearms [11,12]. The results from this study largely confirms the previous work while using a DiD approach to control for confounding variables.…”
Section: Plos Onesupporting
confidence: 80%
See 1 more Smart Citation
“…Mauser and Holmes also found no association with this legislation and firearm homicide [25]. Examination of all three legislative efforts by Langmann resulted in no finding of any beneficial association with overall firearm homicide and spousal homicide by firearm, and McPhedran and Mauser found no association between legislation and homicide of female spouses by firearms [11,12]. The results from this study largely confirms the previous work while using a DiD approach to control for confounding variables.…”
Section: Plos Onesupporting
confidence: 80%
“…The most recent study on overall homicide examined the years 1974 to 2008 and found no associated relationship between homicide rates and firearms legislation enacted in 1977, 1991, and 1995 [11]. Another study looked specifically at homicide of female spouses by firearms and also found no associated benefit with the 1995 legislation, however it did not include any potential explanatory variables such as poverty and unemployment rates [11,12]. A third study examined the legislation enacted in 1991 and found some associated reduction in firearms homicide but this study only examined 7 years pre and post legislation and did not include potential confounders [13].…”
Section: Introductionmentioning
confidence: 99%
“…This enables the present study to detect any impacts that may have occurred in the years immediately following the NFA (thus taking into account possible lag in policy impacts), as well as any changes that may have occurred at other times, unrelated to any likely impacts of firearms legislation. As noted by McPhedran and Mauser (2013), in addition to identifying an endogenous structural break, the ZA test overcomes the difficulty identified by Perron (1989) that in failing to account for a structural break, conventional unit root tests (such as the Augmented Dickey–Fuller [ADF] test) may lead to the incorrect conclusion that the data contain a unit root, when the series is instead stationary around a structural break in the intercept (or “level” of a time series) and/or trend (commonly referred to as slope, or “rate of growth” of a time series). In instances where breaks in trends were detected by ZA tests, further examination of trends pre- and post-breakpoint was undertaken, using simple linear models, to provide indicative statistics about the relative slopes of the pre- and post-breakpoint trends.…”
Section: Methodsmentioning
confidence: 75%
“…Taking into account the value of using more than one test, and following earlier studies, two different analytic approaches were used: Autoregressive Integrated Moving Average (ARIMA) modeling and Zivot–Andrews (ZA) structural breakpoint tests. These methods have been used on similar time series data (Baker & McPhedran, 2007; Langmann, 2012; Lee & Suardi, 2010), including to specifically test the impacts of legislative change on female firearm homicide victimization (McPhedran & Mauser, 2013). Best-fit ARIMA models were selected from examination of Akaike Information Criteria (AIC) and Bayesian Information Criteria (BIC), in conjunction with model fit statistics, and with the stipulations that all resulting predictions be positive values and that the model be both stable and invertible.…”
Section: Methodsmentioning
confidence: 99%
“…An important and comprehensive study by McPhedran and Mauser (2013) focused on gun laws in Canada, searching for a change in trend for female intimate partner homicide incidents. Looking at federal data between 1974 and 2009, the researchers used a sample of homicides between legally married, common-law, separated, and divorced couples who were 15 years old or older.…”
Section: Resultsmentioning
confidence: 99%